Pengaruh Lama Perendaman Kalsium Klorida terhadap mutu Andaliman Effect Of Soaking Time On Andaliman Quality - Roida Ervina Sinaga; Juliana Br Simbolon; Posman HP Marpaung (Universitas Quality, 2019)
Andaliman (Zanthoxylum acanthopodium DC.) is one of exotic plants in Indonesia because its has a unique smell and taste and it grows on a spesific place like dairi regency, north tapanuli, south tapanuli, simalungun and karo regency. This study aim to determine soaking time of andaliman with kalsium klorida concentration 45%. Soaking time consist of 4 type : L1 = 10 Menit, L2 = 20 Menit, L3 = 30 Menit dan L4 = 40 Menit.